Reliability and Validity of the PAQ-C Questionnaire to Assess Physical Activity in Children. - Benítez-Porres, Javier; López-Fernández, Iván; Raya, Juan Francisco; Álvarez-Carnero, Sabrina; Alvero-Cruz, José Ramón; Álvarez-Carnero, Elvis (Wiley, 2016)
BACKGROUND Physical activity (PA) assessment by questionnaire is a cornerstone in the field of sport epidemiology studies. The Physical Activity Questionnaire for Children (PAQ-C) has been used widely to assess PA in healthy school populations. The aim of this study was to evaluate the reliability and validity of the PAQ-C questionnaire in Spanish children using triaxial accelerometry as criterion. METHODS Eighty-three (N = 46 boys, N = 37 girls) healthy children (age 10.98 ± 1.17 years, body mass index 19.48 ± 3.51 kg/m2) were volunteers and completed the PAQ-C twice and wore an accelerometer for 8 consecutive days. Reliability was analyzed by the intraclass correlation coefficient (ICC) and the internal consistency by the Cronbach's α coefficient. The PAQ-C was compared against total PA and moderate to vigorous PA (MVPA) obtained by accelerometry. RESULTS Test-retest reliability showed an ICC = 0.96 for the final score of PAQ-C. Small differences between first and second questionnaire administration were detected. Few and low correlations (rho = 0.228-0.278, all ps < .05) were observed between PAQ-C and accelerometry. The highest correlation was observed for item 9 (rho = 0.311, p < .01). CONCLUSIONS PAQ-C had a high reliability but a questionable validity for assessing total PA and MVPA in Spanish children. Therefore, PA measurement in children should not be limited only to self-report measurements.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/15973
Keywords: Condición física - Evaluación; Ejercicio físico - Niños - Tests; PAQ; Accelerometry; Childhood; Validation; Self-reported physical activity